2019
DOI: 10.1007/s00244-019-00690-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Biomarker Approach in a Commercial Marine Scallop from San Jose gulf (Patagonia, Argentina) for Health Status Assessment

Abstract: The health status of the commercial Tehuelche scallop Aequipecten tehuelchus from San Román and El Riacho in San José gulf (Patagonia, Argentina) was evaluated through biomarkers widely used in ecotoxicological applications. Natural levels of arsenic (As) and cadmium (Cd) were measured to determine their potential relationships with fluctuations of several oxidative stress biomarkers in the scallop. Oxidative biomarkers, such as catalase (CAT), glutathione S-transferase (GST), superoxide dismutase (SOD), metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The medium‐impact samples were mostly characterized by higher concentrations of Cu and Ag, whereas Cd tended to be higher in low‐impact samples (Figure 2C and D). In support of this conclusion, the Argentinian site, classified as low impact, has been monitored for several years by the “Program for monitoring the environmental quality of production areas in the province of Rio Negro,” and has reported natural Cd as the only metal present at high levels (Sturla Lompré et al, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…The medium‐impact samples were mostly characterized by higher concentrations of Cu and Ag, whereas Cd tended to be higher in low‐impact samples (Figure 2C and D). In support of this conclusion, the Argentinian site, classified as low impact, has been monitored for several years by the “Program for monitoring the environmental quality of production areas in the province of Rio Negro,” and has reported natural Cd as the only metal present at high levels (Sturla Lompré et al, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…Different tissues of the oyster M. angulata showed different ranges of variation for the tested biomarkers, with the digestive gland presenting the lowest enzyme activities and total Ubi concentrations. Both gills and digestive glands are usually exposed to both water-borne and food-web xenobiotics due to their role in bivalve feeding processes [46,47].…”
Section: Comparison Between Tissuesmentioning
confidence: 99%
“…The digestive gland has often been identified as the tissue with higher CAT and GST [46,48], since it is largely exposed to contaminants present in the environment and collected with food. Moreover, the digestive gland has also been identified as a tissue in which detoxification is faster, with several biomarkers involved in the detoxification of xenobiotics (e.g., CAT and GST) [46,48].…”
Section: Comparison Between Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, across a large extension of coastal areas of the Argentine Sea, many authors have reported the bioaccumulation of heavy metals in marine invertebrates (Severini et al 2009(Severini et al , 2013Giarratano et al 2010Giarratano et al , 2011Bertrand et al 2016;Buzzi et al 2017;Marinho et al 2018;Villagran et al 2019;) and marine fish (Authman et al 2015;La Colla et al 2017. Also, worldwide information has addressed adverse effects of metals in marine animals, such as erratic swimming of fishes (Bhat and Vamsee 1993), hyperglycemic stress (Lorenzon et al 2000), induction of oxidative stress and oxidative damage (Kim et al 2014;Lompré et al 2019) and inhibition of reproduction (Yi et al 2019).…”
Section: Introductionmentioning
confidence: 99%